2021
DOI: 10.1007/s10147-021-02001-y
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of FOLFIRINOX with primary prophylactic pegfilgrastim for chemotherapy-naïve Japanese patients with metastatic pancreatic cancer

Abstract: Background Although FOLFIRINOX is currently one of the standard therapies for chemotherapy-naïve patients with metastatic pancreatic cancer (MPC), the high rate of febrile neutropenia (FN) presents a clinical problem. This study aimed to evaluate the safety and efficacy of primary prophylactic pegfilgrastim with FOLFIRINOX in Japanese MPC patients. Methods FOLFIRINOX (intravenous oxaliplatin 85 mg/m2, irinotecan 180 mg/m2, levofolinate 200 mg/m2, 5-fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…However, data from subsequent prospective and retrospective studies have shown highly variable rates of G3/4N, ranging from 6 to 78% -Table 5. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In our study, only 23% of the patients developed GN3/4. This is likely related to the relatively high frequency of PP (61%), which showed to be associated with a significantly lower risk of G3/4N (OR = .13) in the multivariate logistic regression.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, data from subsequent prospective and retrospective studies have shown highly variable rates of G3/4N, ranging from 6 to 78% -Table 5. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In our study, only 23% of the patients developed GN3/4. This is likely related to the relatively high frequency of PP (61%), which showed to be associated with a significantly lower risk of G3/4N (OR = .13) in the multivariate logistic regression.…”
Section: Discussioncontrasting
confidence: 56%
“…10,34 However, rates of NF during treatment with FOLFIRINOX are highly variable in the literature, ranging from 0 to 26% -Table 5. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Indeed, the higher figures observed in some retrospective studies have led the NCCN guideline to advise in favor of PP for patients treated with FOLFIRINOX. 1 In our study, only 6.5% of the patients experienced FN and even for those who did not receive PP, the frequency of FN was relatively low (8%).…”
Section: Discussionmentioning
confidence: 99%
“…72,73 The median OS of patients in this Canadian cohort who received gemcitabine 1 nab-paclitaxel after firstline FOLFIRINOX was also higher (19.3 months; 95% CI, 12.6 2 26.0 months) than that in a 2015 clinical trial assessing prophylactic G-CSF use in patients with metastatic PDAC treated with FOLFIRINOX (15.7 months; 95% CI, 7.9-18.8 months). 72,74 In practice, the indications for G-CSF use are dependent on clinical judgment and perceived risk of febrile neutropenia and infectious complications. The potential long-term negative consequences of G-CSF administration in patients with PDAC warrant careful reevaluation of current growth factor support practice guidelines to help clarify its appropriate use.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review showed that prophylactic use of G-CSF reduces the rates of FN, dose reduction, and treatment delay [ 21 ]. Our group previously conducted a phase II trial to evaluate the safety and efficacy of primary prophylactic pegfilgrastim in patients with metastatic pancreatic cancer who received FOLFIRINOX [ 22 ]. However, FN occurred in 18.0% and previously, we could not demonstrate the efficacy of pegfilgrastim addition to FOLFIRINOX; the DV patients were excluded.…”
Section: Discussionmentioning
confidence: 99%